Exploring the Influence of Organizational Culture and Interpersonal Communication on Teacher Performance Through Self-Competency Mediation - Fatah Ansori, Rohmatul; Wit Daryono, Rihab (Jurnal Educative: Journal of Educational Studies, 2024)
This research explores the urgency and influence of organizational culture and interpersonal communication on teacher performance through self-competence. Organizational culture issues often stem from poor communication, a lack of clear vision, resistance to change, and weak collaboration between teams. Ideally, organizational culture should encourage open communication, be rooted in strong values, remain flexible toward innovation, and strengthen teamwork to achieve common goals. The survey method was used to collect data based on probability sampling from 26 teachers from Public Junior High School in Badegan District, Ponorogo, East Java. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis is used to analyze data and test construction infrastructure. The results of the analysis show that Organizational Culture (ẞ=0.086; p=0.562) and self-competence on teacher performance (ẞ=0.268, p=0.099) have an insignificant effect. In addition, self-competence was proven not to mediate the influence of organizational culture (ẞ=0.145: p=0.111) on teacher performance. The implications of this research highlight the important role of organizational culture and interpersonal communication in improving teacher performance.